Diagnostic Value of S100B Protein in Critical Conditions - N. V. Beloborodova; I. B. Dmitriyeva; E. A. Chernevskaya (Общая реаниматология)
The review deals with possibilities for the quantitative assessment of the degree of brain injury, by measuring the level of S100B protein in various biological fluids. Data are given on changes in the concentration of this protein in different categories of patients, including those who are critically ill. Key words: S100B protein, laboratory diagnosis of critical conditions, biomarkers, perinatal brain lesions.